Physiological and neuromuscular impact of beach-volleyball with reference to fatigue and recovery - Magalhaes, J.; Inacio, M.; Oliveira, E.; Ribeiro, J. C.; Ascensao, A. (The Journal of Sports Medicine and Physical Fitness, 2011)
AIM: The aim of the present study was to analyze the physiological and neuromuscular impact of a one 3-set beach-volleyball match and to analyze the ability of the players to recover from fatigue. METHODS: Heart rate (HR) and blood lactate concentration (BLC) were measured in sixteen Portuguese male elite volleyball players during beach-volleyball matches. Vertical countermovement jump (CMJ), sprint (7.5 and 15m) ability and maximal isometric voluntary contraction (MIVC) were evaluated at baseline, immediately (0h) and 3 hours after each match. RESULTS: Mean HR during the match was 146±3 bpm (117±2-185±3 bpm) corresponding to about 75% of HRmax (61-90%HRmax). Players spent 34% of match time above 80% HRmax. BLC during the 3-sets increased from rest (0.95±0.23 vs. 2.10±0.66 [1st-set] vs. 2.41±0.15 [2nd-set] vs. 2.39±0.21mM [3rd-set]). No changes in CMJ were observed at 0 and 3h. Knee extensor and flexor muscles MIVC decreased at 0h (~19 and 17%, respectively) and returned to baseline 3h after. Sprint performance was the only variable that was impaired both at 0h and 3h after the match (~3%). CONCLUSION: Beach-volleyball is performed intermittently at moderate-to-high intensity with brief bouts of high intensity exercise interspersed by long low intensity periods. Match induced a temporary reduction in lower limb strength and sprinting time but 3h after the match all variables with the exception of the sprinting time, that was only slightly reduced, were recovered.